2019
DOI: 10.1002/cphc.201900423
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Gas‐Separation Properties of PVAc‐Zeolite 4A Mixed‐Matrix Membranes through Nano‐Sizing and Silanation of the Zeolite

Abstract: Mixed‐matrix membranes containing synthesised nano‐sized zeolite 4A and PVAc were fabricated to investigate the effect of zeolite loading on membrane morphology, polymer‐filler interaction, thermal stability and gas separation properties. SEM studies revealed that, although the membranes with 40 wt % nano‐sized zeolite particles were distributed uniformly through the polymer matrix without voids, the membranes with 15 wt % zeolite loading showed agglomeration. With increasing zeolite content, the thermal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…In another study by Esmaeili et al. 194, zeolite 4A nanoparticles were added to PVAc as the polymer matrix and their different gas separation performances were investigated. The increment in the amount of zeolite nanoparticles from 15 to 40 wt % caused the permeabilities of all the studied gases (CO 2 , H 2 , N 2 , He) to decrease compared with that of the pure PVAc membrane, but increased their selectivities, i.e., CO 2 /N 2 , He/CO 2 , H 2 /N 2 , H 2 /CO 2 .…”
Section: Gas Separation In Membranesmentioning
confidence: 99%
“…In another study by Esmaeili et al. 194, zeolite 4A nanoparticles were added to PVAc as the polymer matrix and their different gas separation performances were investigated. The increment in the amount of zeolite nanoparticles from 15 to 40 wt % caused the permeabilities of all the studied gases (CO 2 , H 2 , N 2 , He) to decrease compared with that of the pure PVAc membrane, but increased their selectivities, i.e., CO 2 /N 2 , He/CO 2 , H 2 /N 2 , H 2 /CO 2 .…”
Section: Gas Separation In Membranesmentioning
confidence: 99%
“…Among different types of fuel cells, proton exchange membrane (PEM) fuel cells have many advantages, such as low operating temperature, long stack life, compactness, low cost, and fast startups. [ 1–3 ] The core component of PEM fuel cells is the membrane electrode assembly, which is composed of a polymer electrolyte membrane confined between two electrodes. Fabricating high‐performance membrane materials is a major challenge for the effective operation of PEM fuel cells, where the materials need to meet requirements including high proton conductivity (PC), low swelling, and high oxidative and hydrolytic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonated poly(ether ether ketone)s, poly(arylene ether sulfone)s, poly(sulfones), poly(benzimidazoles), and their derivatives have been studied most intensively. [ 2,5–7 ] For hydrocarbon‐based membranes, a higher degree of sulfonation is necessary in order to achieve high PC, since the acid strength of the sulfonic acid groups in these materials is significantly lower than in perfluorosulfonic acid‐based membranes. [ 8 ] Furthermore, it was observed that the phase separation and thus the formation of proton‐conducting channels in hydrocarbon‐based systems is less pronounced than in Nafion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the contribution of the nanofillers to MMMs enhances the thermal stability of the membranes without considerable adverse effect on the processability of the membranes . Typical fillers used in these membranes include metal oxides, zeolites, two‐dimensional (2D) nanomaterials, covalent organic frameworks, and metal–organic frameworks (MOFs) . Although it has been observed that separation properties of polymeric membranes improve by adding inorganic fillers, there are still some technical challenges in the selection of proper polymer matrix and inorganic fillers.…”
Section: Introductionmentioning
confidence: 99%